The Rolef Organizational Citizenship Behavior in Mediating the Influence of Transformational Leadership and Job Satisfaction on the Performance Of PT Employees. Safari Wonder Bali in Gianyar District - WIDYAWATI, Dewa Ayu; PUTRA, Ida Bagus Udayana; AMERTA, I Made Suniastha (International Journal of Environmental, Sustainability, and Social Science, 2024)
PT. Safari Wonders Bali is one of the business units of Taman Safari Indonesia, which operates in the retail sector and sells souvenirs from Taman Safari Indonesia. This research examines organizational citizenship behavior's role in mediating the influence of transformational leadership and job satisfaction on employee performance. The number of samples used in this research was 51, and the hypothesis was tested using SEM-PLS inferential data analysis. This research shows that transformational leadership has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Transformational leadership has a positive and significant effect on OCB. Job satisfaction has a positive and insignificant effect on OCB. OCB has a positive and significant effect on employee performance. OCB mediates the influence of transformational leadership on employee performance. OCB does not mediate the effect of job satisfaction on employee performance. This research implies that the relationship between transformational leadership and employee performance, job satisfaction and employee performance, transformational leadership and OCB, and the relationship between OCB and employee performance are real.